Numerical study of the laminar flow and heat transfer characteristics in a tube inserting a twisted tape having parallelogram winglet vortex generators. (25th March 2017) - Lin, Zhi-Min; Wang, Liang-Bi; Lin, Mei; Dang, Wei; Zhang, Yong-Heng
Abstract: The usage of wings or/and winglets vortex generators (VGs) could provide excellent heat transfer performance with a minimal increase in pressure loss comparing with other VGs in a wide range of Reynolds number. For classical twisted tape, the contact area between twisted tape and working fluid is large, which would result in high friction drag. Motivated by this fact, a newly designed twisted tape having parallelogram winglet VGs (PWVGs) is proposed to enhance heat transfer. This twisted tape with winglet VGs is formed by cutting at the edge of the straight tape with parallelogram shape to produce a parallelogram winglet as twisting around its longitudinal axis. The laminar fluid flow and conjugate heat transfer characteristics in a circular tube inserting the twisted tape with PWVGs were analyzed using numerical method under uniform wall temperature condition, and four different attack angle α ( α  = 27.64°, 21.44°, 17.44° and 14.67°) and four different axial spacing S t ( S t  = 0.83 D, 1.0 D, 1.25 D and 1.67 D ). The results show that (1) the newly designed twisted tape has two ways to generate secondary flow, including secondary flow generated by the twisted base tape and extra secondary flow generated by PWVGs; (2) the combination of twisted base tape and PWVGs has evident effects on the local flow and heat transfer characteristics; (3) compared with the reference empty tube, the twisted tape with PWVGs can effectively enhance heat transfer under identical pumping power condition, for studied case of α  = 17.44°, S t / D  = 1.25 and Re ranging from 50 to 600, the average Nusselt number and friction factor are increased by 76.4–190.9% and 179.9–289.1%, respectively, and the corresponding thermal performance factor ranges from 1.25 to 1.85; and (4) as Re ranges from 50 to 600, the helical angle α of PWVGs is a very important parameter in design of the modified twisted tape, and when α is large and S t is small the heat transfer performance of the twisted tape with PWVGs is better.